CORRELAÇÕES GENOTÍPICAS, FENOTÍPICAS E AMBIENTAIS EM ALGODOEIRO (GOSSYPIUM HIRSUTUM L. VAR. LATIFOLIUM HUTCH.) - CARVALHO, LUIZ PAULO DE; CRUZ, COSME DAMIÃO; MORAES, CARLOS FLORIANO (Revista Ceres, 2015)
.